2021
DOI: 10.26434/chemrxiv.14579259
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In Situ Probing Potassium-ion Intercalation-induced Amorphization in Crystalline Iron Phosphate Cathode Materials

Abstract: <p>Na-ion and K-ion batteries are promising alternatives for large-scale energy storage applications due to their abundancy and lower cost. However, designing an electrode structure to reversibly accommodate these large alkali-ions is the remaining challenge before their commercialization. Intercalation of these large ions could cause irreversible structural deformations and amorphization in the crystalline electrodes. The designing of new amorphous electrodes is another route to develop electrodes to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…[ 26 ] A recent in situ XRD study also demonstrated the amorphization of the crystalline iron phosphate during the intercalation of K ions. [ 21 ]…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…[ 26 ] A recent in situ XRD study also demonstrated the amorphization of the crystalline iron phosphate during the intercalation of K ions. [ 21 ]…”
Section: Resultsmentioning
confidence: 99%
“…XRD studies on K ion intercalation into iron phosphate demonstrated amorphization in the crystalline structure. [ 19,21 ] Therefore, progressive evolution of the strain rates in the electrodes is likely due to the occurrence of plastic deformation in the electrode structure. Constant strain rates during Li and Na intercalation can be interpreted as preserving crystalline structure while removing these ions from the host structure.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations